Strengthening Vocational Students’ English Competence Through Technology-Supported Instruction - Putra, Rizky; Febria, Desty; Zaki, Leil Badrah (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2025)
This research focuses on examining how technology supports English language learning in the specific context of vocational high schools. Using a mixed-methods design, data were collected through questionnaires and interviews to capture students' perceptions and learning experiences. The research participants included 20 eleventh-grade students and one English teacher from a private vocational high school in Batam. The findings show that students expressed high enthusiasm for technology-based learning, especially in improving their writing skills and participating in group-based activities. Technology was also reported to increase motivation and participation, although challenges such as device limitations and school regulations were also noted. This research highlights the need for careful integration of digital tools in English language learning in vocational schools and recommends further research involving younger students preparing for higher education. The implication of this research is that technology can enhance English learning in vocational high schools by increasing students’ motivation, participation, and skill development especially in writing and collaborative tasks.